Analisis Kinerja Pegawai di Badan Kepegawaian dan Pengembangan Sumber Daya Manusia (BKPSDM) Lubuk Pakam - Waizul Qarni, Heldia Fitri, (Invention: Journal Research and Education Studies, 2022)
The purpose of this study was to determine the analysis of employee performance in the Agency for Personnel and Human Resources Development in Lubuk Pakam. The research method used in this study is to use a quantitative approach, namely to provide a clear picture of the problem under study. Explaining data systematically at the Agency for Personnel and Human Resources Development by collecting data by questionnaires, observations and studies on matters related to this research. The factors that affect the performance of employees at BKPSDM are in terms of work ability, work motivation and job opportunities. From this study, it can be concluded that the performance of employees at the Lubuk Pakam Personnel and Human Resources Development Agency is very good. Judging from the high percentage of measuring the value of the questionnaire on work ability (84.45), work motivation (86.23%) and opportunities (86.16%) however, it should be increased to very good again.